PENDIDIKAN BERBASIS TEKNOLOGI - Evi Anggraini; Lidya Nababan Aprilliana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The development of the world of education at this time is certainly not free from the development of information technology which participates in all aspects. One of them is the internet, the internet is a revolution that changes our system of life as a civilized society and seeks to advance the welfare of its life through a continuous education process, and as one of the supporting factors for the advancement of education in Indonesia has positive and negative impacts. The role of the internet on the education system as a service provider of information quickly is used for teachers and students. The most potential benefits of the internet in addition to administrators and interested parties in the environment is to facilitate the collection of school data sheets that can be sent directly to the destination both individuals and the wider community.